Functional Characterization of Two Putative DAHP Synthases of AroG1 and AroG2 and Their Links With Type III Secretion System in Ralstonia solanacearum - Zhang, Weiqi; Li, Jing; Shi, Xiaojun; Hikichi, Yasufumi; Zhang, Yong; Ohnishi, Kouhei (Frontiers in Microbiology, 2019)
DAHP synthase controls the first step of shikimate pathway that is a common route for biosynthesis of aromatic amino acids (AAA) in microorganisms and plants. Here, we genetically characterized two putative DAHP synthases of AroG1 and AroG2 in Ralstonia solanacearum, a causal agent of bacterial wilt on many plant species. Growth in limited medium was diminished in aroG1/2 mutants, significantly impaired in aroG1 mutants, but not in aroG2 mutants. Supplementary AAA or shikimic acid, an important intermediate of shikimate pathway, significantly restored the diminished growth, suggesting that AroG1 and AroG2 are cooperatively responsible for AAA biosynthesis through shikimate pathway. Whereas aroG1/2 mutants could thrive in host plants although they grew much slowly in host plants. Deletion of aroG1 or aroG1/2, but not aroG2, significantly reduced expression of Type III secretion system (T3SS) both in vitro and in planta, which is essential for pathogenicity, and impact of AroG1 on T3SS was mediated with the well-characterized PrhA signaling cascade. Deletion of aroG1 or aroG1/2, but not aroG2, diminished virulence on tomato plants. Complementary aroG1 significantly restored diminished growth, T3SS expression and virulence. Promoter activity assay showed expression of aroG1 and aroG2 remained at relatively low levels, while it was greatly increased with deletion of the other, indicating the bacterium could feedback greatly enhance aroG1 expression to fulfill growth and virulence in absence of AroG2. AroG1 plays a major role on growth, T3SS and pathogenicity, while AroG2 is supplementary for AroG1 that could partially substitute AroG1 mainly in absence of AroG1.